Exploring the role of ectomycorrhizal fungi in soil carbon dynamics. Issue 1 (8th February 2019) - Zak, Donald R.; Pellitier, Peter T.; Argiroff, WilliamA.; Castillo, Buck; James, Timothy Y.; Nave, Lucas E.; Averill, Colin; Beidler, Kaitlyn V.; Bhatnagar, Jennifer; Blesh, Jennifer; Classen, Aimée T.; Craig, Matthew; et al.
Summary: The extent to which ectomycorrhizal (ECM) fungi enable plants to access organic nitrogen (N) bound in soil organic matter (SOM) and transfer this growth‐limiting nutrient to their plant host, has important implications for our understanding of plant–fungal interactions, and the cycling and storage of carbon (C) and N in terrestrial ecosystems. Empirical evidence currently supports a range of perspectives, suggesting that ECM vary in their ability to provide their host with N bound in SOM, and that this capacity can both positively and negatively influence soil C storage. To help resolve the multiplicity of observations, we gathered a group of researchers to explore the role of ECM fungi in soil C dynamics, and propose new directions that hold promise to resolve competing hypotheses and contrasting observations. In this Viewpoint, we summarize these deliberations and identify areas of inquiry that hold promise for increasing our understanding of these fundamental and widespread plant symbionts and their role in ecosystem‐level biogeochemistry.